Web application development process - Ibrahim, Adamu Abubakar; Mantoro, Teddy (IIUM Press, 2011)
There are a lot of challenges when it comes to the developing of the right web site with the application at the right time. Web sites that initially started as a few Web pages grew in size and after a while became unmanageable. There are a lot of cases where managers wanting to develop Web sites for their organizations getting frustrated because they could not get the Web site they wanted to developed in a timely manner within a reasonable budget. Another common downside occurrence is that if an information change,appropriate changes to all relevant Web pages becomes very difficult. Although, by performing a context analysis and developing a product model and a process model before going into the details will be able to allow developers to meet the client I user requirements. Unfortunately, information are dynamic, each day there are onward addition of updates and subtraction of outdate these however remain as a strong challenges, as a result this chapter provide some possible ways of respond to some challenges faced while developing a particular web site called "Peer Student Portal". A highdegree of client-user participation (problem analysis), testing (as the measure issue) and flexibility of web application has been recognized to be some of the major critical activities during web development